Evaluation of Electrode Materials for All-copper Hybrid Flow Batteries - Puiki, Leung; Jesus, Palma; Enrique, Garcia-Quismondo; Laura, Sanz; Mohd Rusllim, Mohamed; Marc, Anderson (Elsevier Ltd, 2016)
This work evaluates a number of two- and three-dimensional electrodes for the reactions of an all-copper hybrid flow battery. Half- and full-cell experiments are conducted by minimizing the crossover effect of the copper(II) species. The battery incorporates a Nafion® cation exchange membrane and the negative electrolyte is maintained at the monovalent (colourless) state by the incorporating copper turnings in the electrolyte reservoir. Under such conditions, the half-cell coulombic efficiencies of the negative electrode reactions are all higher than 90% regardless of electrode materials and the state-of-charge (SOC). With charge–discharge cycling the half-cell from a 0% SOC, the coulombic efficiencies of the positive electrode reactions are lower than 76% with the planar carbon electrode, which further decrease in shorter charge–discharge cycles. Polarization and half-cell charge–discharge experiments suggest that the high-surface-area electrodes effectively reduce the overpotentials and improve the coulombic efficiencies of both electrode reactions. When copper fibres and carbon felt are used as the negative and positive electrodes, the average coulombic and voltage efficiencies of an all-copper flow battery are as high as c.a. 99% and c.a. 60% at 50 mA cm−2 for 35 cycles.